Organic carbon burial and sources in soils of coastal mudflat and mangrove ecosystems - Sasmito, Sigit D.; Kuzyakov, Yakov; Lubis, Ali Arman; Murdiyarso, Daniel; Hutley, Lindsay B.; Bachri, Samsul; Friess, Daniel A.; Martius, Christopher; Borchard, Nils (Catena (Giessen), 2020)
[Display omitted] •Organic carbon burial rates and sources were assessed across Papuan mangroves.•Organic carbon burial rates ranged between 0.21 and 1.19 Mg C ha−1 yr−1.•Soil organic carbon stocks in the top 50 cm varied between 62 and 179 Mg C ha−1.•Soil organic carbon stocks are sourced from autoch- and alloch-thonous sources. Mangrove organic carbon is primarily stored in soils, which contain more than two-thirds of total mangrove ecosystem carbon stocks. Despite increasing recognition of the critical role of mangrove ecosystems for climate change mitigation, there is limited understanding of soil organic carbon sequestration mechanisms in undisturbed low-latitude mangroves, specifically on organic carbon burial rates and sources. This study assessed soil organic carbon burial rates, sources and stocks across an undisturbed coastal mudflat and mangrove hydrogeomorphological catena (fringe mangrove and interior mangrove) in Bintuni Bay, West Papua Province, Indonesia. 210Pb radionuclide sediment dating, and mixing model of natural stable isotope signatures (δ 13C and δ15N) and C/N ratio were used to estimate organic carbon burial rates and to quantify proportions of allochthonous (i.e., upland terrestrial forest) and autochthonous (i.e., on-site mangrove forest) organic carbon in the top 50 cm of the soil. Burial rates were in the range of 0.21–1.19 Mg C ha−1 yr−1. Compared to the fringe mangroves, organic carbon burial rates in interior mangroves were almost twice as high. Primary productivity of C3 upland forest vegetation and mangroves induced soil organic carbon burial in interior mangroves and this was consistent with the formation of the largest organic carbon stocks (179 ± 82 Mg C ha−1). By contrast, organic carbon stored in the fringe mangrove (68 ± 11 Mg C ha−1) and mudflat (62 ± 10 Mg C ha−1) soils mainly originated from upland forests (allochthonous origin). These findings clearly indicate that carbon sequestered and cycling in mangrove and terrestrial forest ecosystems are closely linked, and at least a part of carbon losses (e.g., erosion) from terrestrial forests is buried in mangrove ecosystems.